Portfolio Hedging and Basis Risk - Lim, Kian Guan (Institutional Knowledge at Singapore Management University, 1996)
Minimum variance hedged portfolios using futures are formed by taking the linear projection of spot price changes onto futures price movements as the hedge ratio. This unwittingly assumes that the underlying spot-futures price movements follow a cointegrated process, given that the spot and the futures prices are integrated processes. If the spot-futures prices are not cointegrated, the hedged portfolio suffers from the risk of potentially large changes in its value. Empirical findings using the Nikkei stock index and the Nikkei 225 futures show this deviation in intraday trading prices. The basis movements which have often been used by intraday traders to predict future price changes, are tested to be mostly unit root processes. This is shown to be due largely to non-cointegration of the spot-futures prices, and suggests why it is profitable to trade futures using basis knowledge only if trading is done on a continual basis.